Characterising the cardiac effects of dysregulated propionate metabolism using a mouse model of propionic acidaemia - Park, KC (2021)
Propionate is a naturally-occurring monocarboxylate short-chain fatty acid in humans derived from the mitochondrial metabolism of multiple substrates. There is evidence for dysregulated propionate metabolism (and hence its accumulation), in common metabolic disorders, such as diabetes and obesity. However, the most extreme accumulation of propionate occurs in the inherited metabolic disease, propionic acidaemia (PA). Despite its rarity, PA is one of the commonest organic acidaemias. PA results from a defect in mitochondrial propionyl-CoA carboxylase, the rate-limiting step to propionate metabolism (as propionyl-CoA), resulting in the accumulation of propionate, and other related metabolites such as propionyl-carnitine and 2-methylcitrate. Interestingly, diastolic dysfunction, cardiomyopathy and arrhythmias account for significant morbidity and mortality in PA patients. However, the underlying mechanisms are yet to be fully elucidated.